On the role of collegiality, civility and collectivism in shaping academic identity. (2nd July 2016) - Macneil, Johanna
ABSTRACT: This paper considers how the values of industrial relations scholars affect their academic identity. The specific values considered are collegiality, civility and collectivism. The meaning of these values in academia is reviewed, along with some of their inherent contradictions and the challenges posed by their implementation in contemporary academic working life. The paper concludes with suggestions about how a scholarly association can help support and strengthen academic values, and a call for scholars to reflect on what makes academic life rewarding and how to retain it.